The effects of symmetric center of pressure displacement training with feedback on the gait of stroke patients - Kim, Jin-Seop (Journal of Physical Therapy Science, 2015)
[Purpose] This study investigated the effects of COP displacement training using visual feedback had on the gait of patients with hemiplegia due to stroke. [Subjects and Methods] This study was conducted with 20 patients with hemiplegia due to stroke. The training consisted of five training sets repeated 10 times and the activity was conducted for 15 minutes each session, three times per week for six weeks immediately after completion of central nervous system developmental treatment. [Results] A comparison of the results of before and after the experiment found that the COP displacement training group showed significant improvements in step length, stride length, gait velocity, and the functional reach test, while the control group showed significant improvement only in the functional reach test. In the intergroup comparison, the COP displacement training group showed significant improvements in paretic side step length, paretic side stride length, gait velocity, and the functional reach test compared to the control group. [Conclusion] In conclusion, according to the results of this study, visual feedback training for COP displacement is more effective at enhancing the gait and balance of hemiplegic patients due to stroke than only performing feedback training for even weight distribution.